NON-ALCOHOLIC FATTY LIVER DISEASE - Gafforov Xudoyor Xudoyberdiyevich (Scholar Express Journals, 2023)
In recent decades, there has been an increase in non-alcoholic fatty liver disease (NAFLD), which not only leads to a decrease in the quality of life of patients, but also affects their life expectancy. Fatty hepatosis or non—alcoholic fatty liver disease (NAFLD, steatosis) is a disease in which excessive accumulation of fats (mainly triglycerides) is observed in the liver. Normally, there is a certain amount of fat in the liver, but when exposed to certain pathological factors, the balance between the synthesis and utilization of fats may be disturbed. The prevalence of NAFLD is higher among men and increases with age, due to socio-economic differences and lifestyle. In the general population of Western countries, the prevalence of NAFLD is 20-30%, of which 2-3% of cases have a progressive course of liver disease with transformation into non-alcoholic steatohepatitis (NASH), cirrhosis of the liver, hepatocellular carcinoma. The triglyceride content in NAFLD can reach 40% of the liver weight (at a rate of about 5%). NAFLD develops in three stages — steatosis, non-alcoholic steatohepatitis (NASH) and fibrosis. NAFLD often proceeds unnoticed, almost asymptomatic. The essence of the disease is liver obesity, the replacement of a normal healthy liver with fat, which leads to cirrhosis, like any other liver diseases, including viral hepatitis.The most significant risk factors are male gender, obesity, increased waist circumference, metabolic syndrome, insulin resistance and type 2 diabetes mellitus (DM).
Keywords: non-alcoholic fatty liver disease; lifestyle; steatohepatitis